Cardiac resynchronization therapy induced QRS narrowing: could it change the prognosis?. (3rd May 2023) - Duarte, F; Santos, I; Barradas, M; Monteiro, A; Dourado, R; Martins, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac resynchronization therapy (CRT) responders should have symptomatic improvement and benefits in long-term outcomes. CRT is indicated in the treatment of heart failure (HF) patients with systolic dysfunction and prolonged QRS duration. There are conflicting results regarding QRS narrowing on CRT response. Objective: We ought to access the impact of QRS narrowing after CRT implantation in clinical outcomes and arrhythmic events. The association between the QRS duration reduction in responders and non-responders was determined. Methods: We retrospectively enrolled 110 consecutive patients with CRT. Native QRS duration and QRS duration at least 6 months after procedure were determined by EKG. Baseline clinical characteristics were accessed. Three outcomes were created. Primary outcome: hospitalization or emergency department admissions due to HF decompensation. Secondary outcome: sustained ventricular arrhythmic events. Tertiary MACE outcome (composite of cardiovascular death, hospitalization due to HF or acute coronary syndrome and cerebrovascular events). Results: Out of 110 patients included, the mean age was 70.3 ± 10.7 years, 68.2% were male and mean body mass index was 29.1 ± 5.7 kg/m2. Baseline characteristics were similar between genders: 41.1% had atrial fibrillation, 10.3% peripheral arterial disease, 72.9% hypertension, 66.4% dyslipidemia, 44.9% diabetes and 20.7% chronic kidney disease. Ischemic etiology (p 0.001), pulmonary lung obstructive disease (p <0.001; r=0.35) and smoking habits (p <0.001; r=0.5) prevailed in male patients. Responders by clinical and/or echocardiographic criteria were 62.7%. Native QRS mean duration was 162.4 ± 22 ms and mean QRSd after CRT was 141.9 ± 37 ms, with a median QRS narrowing of 20 ± 30 ms. Primary outcome occurred in 28.6%, secondary in 16.4% and MACE occurred in 31.8%. QRS narrowing was an independent predictor of primary and secondary outcomes (U 283; p 0.016 and U 110.5; p 0.043) as well as MACE (U 6.18; p 0.035). ROC curve analysis compared native and post-CRT implantation QRSd and their impact on outcomes. The best cut-off values for hospitalization and MACE were 10 and 13, respectively (AUC 0.69; 95% CI 0.54 – 0.84; p 0.016 and AUC 0.64, 95% CI 0.52 – 0.76; p 0.035). Conclusion: Patients with a larger decrease in QRS duration after CRT implantation revealed improved outcomes and it was independent of CRT response. This variable could be of interest in selecting HF patients for CRT.